COMPARATIVE EFFECTIVENESS OF ENTECAVIR VERSUS TENOFOVIR FOR PREVENTING HEPATOCELLULAR CARCINOMA IN PATIENTS WITH CHRONIC HEPATITIS B: A COMPREHENSIVE SYSTEMATIC REVIEW - Ayyub; Suwandhi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Chronic hepatitis B (CHB), a hepatotropic infection affecting over 250 million people worldwide is associated with a long-term risk of hepatocellular carcinoma (HCC), the most common primary cancer of the liver. HCC incidence is increasing; it is the fifth most common cause of cancer worldwide, and the third leading cause of cancer-related death. The aim: The aim of this study to show about comparative effectiveness of entecavir versus tenofovir for preventing hepatocellular carcinoma in patients with chronic hepatitis B. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 20 articles, whereas the results of our search on SagePub get 47 articles, on Google Scholar 8810 articles. Records remove before screening are 6028, so we get 2849 articles fos screening. After we screened based on record exclude, we compiled a total of 12 papers. We included five research that met the criteria. Conclusion: Entecavir (ETV) and tenofovir disoproxil fumarate (TDF) have remained the first-line antiviral agents in several international guidelines. These two antiviral agents have shown similar short to intermediateterm efficacy, including virologic, biochemical, serologic, and histologic responses. However, huge controversies regarding the antiviral efficacy of ETV and TDF in preventing the development of hepatocellular carcinoma (HCC).